El aprendizaje colaborativo y su aplicación en la formación de los estudiantes de la maestría en educación a distancia, modalidad B-Learning, en el periodo 2009-2010 - Hernández Rojas, Manuel Ángel (2012)
The main goal of this research work is to analyze the incidence that the application of the Collaborative Learning – CL has had in the formation process of the Students of the Mastery in Distance Education – DE, b-learning modality, of the Program of Distance Education of PROMADIS of the National University of Loja. The main methods, techniques and procedures used to collect the data and to obtain the results have been the well known such as the inductive, deductive, analytical-synthetic, heuristic, hermeneutic among others. But, also other new methods have been used such as the syncretic and the transegic. The techniques are the orthodox ones like the survey, interview, observation, but all them applied in a new electronic, digital and virtual version with the help of other technological tools like internet, telephone, chat room, email, skype, live messenger, facebook, twitter, among others. The main results obtained from the research process are within the lack of an knowledge production in a significant level, also the still cognitive dependence, the presentation of just a few great innovative; all of this as a result of an inefficient application of the collaborative learning CL. Among the most important conclusions we got that: It’s compulsory to develop the scientific and technological creativity in a higher level. There is still a high cognitive dependence, this means that there is a lack of capacity to generate our own ideas in the academic, scientific, technological, philosophical and epistemological fields with a worldwide competence. There is still a lack of innovative proposals in order to improve the formation and other proces